2018
DOI: 10.3389/fmicb.2018.02737
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Community Structure and Microbial Activity in a Traditional Organic Milpa Farming System Under Different Soil Moisture Conditions

Abstract: Agricultural practices affect the bacterial community structure, but how they determine the response of the bacterial community to drought, is still largely unknown. Conventional cultivated soil, i.e., inorganic fertilization, tillage, crop residue removal and maize (Zea mays L.) monoculture, and traditional organic farmed soil “milpa,” i.e., minimum tillage, rotation of maize, pumpkin (Cucurbita sp.) and beans (Phaseolus vulgaris L.) and organic fertilization were sampled. Both soils from the central highland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 85 publications
1
19
0
1
Order By: Relevance
“…Similarly, nutrient and residue management practices such as the application of chemical fertilizers often influence the endogenous microbial communities (Fierer et al, 2007). However, soil bacterial diversity is known to be affected by the numerous environmental factors including soil pH (Lauber et al, 2009;Cho et al, 2016;Sánchez-Cañizares et al, 2017), the chemistry of soil organic matter (Lupatini et al, 2017), plant species grown in the soil (Yamamoto et al, 2018), secretion of different root exudates by the plant species (Sasse et al, 2018;Huang et al, 2019), and processing of the soil before the cultivation of the plants (Moreno-Espíndola et al, 2018). Plant root exudates primarily stimulate the microbial activity in the rhizosphere, resulting in increased microbial active biomass and abundance in the rhizosphere by several folds in comparison to surrounding bulk soil (Lugtenberg and Kamilova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, nutrient and residue management practices such as the application of chemical fertilizers often influence the endogenous microbial communities (Fierer et al, 2007). However, soil bacterial diversity is known to be affected by the numerous environmental factors including soil pH (Lauber et al, 2009;Cho et al, 2016;Sánchez-Cañizares et al, 2017), the chemistry of soil organic matter (Lupatini et al, 2017), plant species grown in the soil (Yamamoto et al, 2018), secretion of different root exudates by the plant species (Sasse et al, 2018;Huang et al, 2019), and processing of the soil before the cultivation of the plants (Moreno-Espíndola et al, 2018). Plant root exudates primarily stimulate the microbial activity in the rhizosphere, resulting in increased microbial active biomass and abundance in the rhizosphere by several folds in comparison to surrounding bulk soil (Lugtenberg and Kamilova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the impact of the cropping system is considered to be stronger than any potential spatiotemporal variations [74]. The effect of the different cropping systems was not reflected in the dominant bacterial phyla, contrary to that observed by Lupatini, et al [73] or Moreno-Espíndola et al [75]. Hartman et al [74] observed that differences in the bacterial community between organically farmed and conventionally managed soils under integrated fertilization were smaller.…”
Section: Discussionmentioning
confidence: 90%
“…Under our experimental conditions, Actinobacteria and Chloro exi phylum increased in HI plots. Accordingly, it was previously reported Moreno-Espíndola et al [60] in an organic Milpa farm with different moisture, thus these authors suggested that phylotypes belonging to Actinobacteria and Chloro exi were enriched in dry conditions because their thick cell walls, lamentous growth and spore formation favor them under dry conditions [61]. In contrast, Vink et al [56] found little variation in Actinobacteria and Proteobacteria proportions between the different cultivars, the phenological stages and irrigation treatments.…”
Section: Bacterial and Fungal Composition After Amf Inoculation And Irrigation Treatment Application During The Seasonmentioning
confidence: 85%